The Russian school of violin the legacy of Yuri Yankelevich - Lankovsky, Masha ca. 20./21. Jh; Lankovsky, Masha ca. 20./21. Jh (Oxford University Press, 2016)
'The Russian School of Violin' is an English translation of the methodological works by Yuri Yankelevich, one of the most important violin teachers of 20th century Russia. Casting an entirely new light on the Russian Violin School, this book includes two original texts by Yankelevich addressing positioning and shifting along with material by prominent violinists examining his pedagogy